2005
DOI: 10.1007/s10640-005-0069-2
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic Dominance Analysis of Soil and Water Conservation in Subsistence Crop Production in the Eastern Ethiopian Highlands: The Case of the Hunde-Lafto Area

Abstract: The aim of this paper is to analyze whether investment in soil and water conservation results in a higher yield and income and/or mitigate variability in yield and income to subsistence farm households in the Hunde-Lafto area. Net returns from crop production with and without soil and water conservation (SWC) are compared based on stochastic dominance (SD) criteria. A non-parametric first order SD and normalized second order are used for data analysis. Analysis is based on the Soil Conservation Research Progra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 14 publications
1
14
0
Order By: Relevance
“…Most of these studies, however, have a bias towards soil conservation as a productivity-enhancing technology. In moisture-stressed area of eastern Ethiopia, Bekele's (2005) research showed that plots with soil bunds 5 produce higher yields than those without. Kassie and Holden (2006) used cross-sectional farm-level data to demonstrate that in high rainfall areas, such as those in northwestern Ethiopia, fanya-juu terracing has no productivity gains.…”
Section: Previous Researchmentioning
confidence: 98%
“…Most of these studies, however, have a bias towards soil conservation as a productivity-enhancing technology. In moisture-stressed area of eastern Ethiopia, Bekele's (2005) research showed that plots with soil bunds 5 produce higher yields than those without. Kassie and Holden (2006) used cross-sectional farm-level data to demonstrate that in high rainfall areas, such as those in northwestern Ethiopia, fanya-juu terracing has no productivity gains.…”
Section: Previous Researchmentioning
confidence: 98%
“…For instance, studies have shown that farming decisions that include farm managers employing soil bunds and terracing to control runoff and soil erosion produce higher yields (Benin, 2006;Pender & Gebremedhin, 2006;Bekele, 2005). The economic returns on physical soil and water conservation investments, as well as their impacts on productivity have been shown to be positive and significant (Shively, 1998;Gebremedhin et al, 1999;Kassie et al, 2008).…”
Section: Analytical Framework For Assessing Land Management Practicesmentioning
confidence: 99%
“…Using stochastic dominance analysis (SDA) and non-experimental farmlevel data collected in the Philippines, Shively (1999) compared observed yields obtained from farmers' fields with and without contour hedgerows and found that the use of hedgerow technology did not constitute an unambiguously dominant production strategy. Yet, Bekele (2005), using SDA and results from experimental trials of the Soil Conservation Research Project in a low-rainfall 1 Literally, fanya juu means "throw soil uphill" in Swahili. In a fanya juu bund, a ditch is dug along a contour around a plot, and the soil is thrown uphill to form a ridge to block soil movements.…”
Section: Literature Reviewmentioning
confidence: 99%